China-Russia relations in a framework of strategic containment - Freire, Maria Raquel (2021)
This article analyses Russian foreign policy in its Asian dimension, placing Russia’s relationship with China in the broader framework of Russia’s foreign policy “Asia Pivot” strategy. The study concludes with a cautious reading of this relationship, anchored in the notion that, underneath the layer of greater closeness and intensified collaboration, lies a relationship of double strategic containment, both regarding the US and the West, and between these two giants. For Russia, the relevance of China in political and economic terms is evident and clearly assumed, but the fear of imbalances resulting from substantive differences between the two has held back a number of actions, while encouraging others in a logic of much-needed refocusing and rebalancing for Moscow.